Physiological responses and activity demands remain consistent irrespective of team size in recreational handball - Nenad Stojiljković; Aaron Scanlan; Vincent Dalbo; Ratko Stankovic; Zoran Milanović; Emilija Stojanović (Termedia Publishing House, 2020)
The aim of this study was to examine the impact of team size on acute physiological, perceptual, and activity demands of recreational handball to provide a better understanding for the potential prescription of recreational handball to achieve health benefits. Active, male college students (N=22) completed 3-, 4-, and 5-a-side handball game formats across three separate sessions following a repeated-measures, crossover design. Heart rate (HR), blood lactate concentration (BLa), rating of perceived exertion (RPE), distance covered, and frequency of accelerations/decelerations were monitored during games. Each game format elicited vigorous intensities with a mean HR in the range 82-85%HRmax and post-game BLa in the range 3.9-4.4 mmol·L-1. No significant differences (P>0.05) in absolute (ηp2=0.40), relative mean HR (ηp2=0.43), BLa (ηp2=0.16), total distance (ηp2=0.32), total accelerations (ηp2=0.23), or total decelerations (ηp2=0.23) were observed between game formats. A significant effect was observed for RPE (ηp2=0.51), where 3-a-side games elicited a higher RPE than 5-a-side games (P=0.03, large). Modifying player number has a negligible effect on the physiological and activity demands encountered during recreational handball games. Recreational handball consisting of 3-5 players imposes similar intermittent workloads, resulting in vigorous physiological responses concomitant with those recommended for overall health improvements as part of regular training.